Field control of Herpetogramma licarsisalis (Walker) in northern Northland pastures - Hardwick, S.; Davis, L.T. (New Zealand Plant Protection, 2000)
Two field trials and one laboratory bioassay were used to evaluate insecticides for the control of Herpetogramma licarsisalis a new arrival infesting kikuyu pastures in northern Northland In both field trials larval densities in plots treated with chlorpyrifos diazinon alphacypermethrin diflubenzuron triflumuron and Bacillus thuringiensis were significantly lower than those in the control plots 14 days after treatment application In the laboratory 80100 larval mortality occurred after eight days exposure to kikuyu foliage treated with the above insecticides (P